Whistler wavas self-focusing laboratory and ionospheric plasmas in density troughs - Davydova, T.A.; Yakimenko, A.I. (Вопросы атомной науки и техники, 2003)
Stationary self-focusing of whistler waves, which propagate along magnetic field with frequencies below half electron-cyclotron frequency is considered in the framework of two-dimensional generalized nonlinear Schroedinger equation. It takes into account electrostatic wave component of whistler waves and nonlocal nonlinearity caused by plasma heating during intense whistler wave propagation, which may be essential in laboratory plasma and in ionospheric experiments. Necessary conditions for stationary nonlinear self-trapping in self-sustained waveguides are found and their stability confirmed both analytically and numerically.